M-Learning Based Remote Laboratory for Electronics Experiments - M V, Ramya; G K, Purushothama; Prakash, K R (International Journal of Online and Biomedical Engineering (iJOE), 2020)
The paper goals on the implementation of Mobile learning (M-learning) based Remote Laboratory to maximize the available resource as well as to improve self learning ability. The developed system provides practical experience to the learners in the field of analog electronics. This laboratory permits the learners to conduct experiments on real time with the internet facility using developed android mobile application. A characteristic of Junction Field Effect Transistors (JFET’s) related to analog electronics has been considered for remote laboratory experimentation. The designed system can be expanded by adding new experiments without any complexity. This M-learning based remote laboratory approach enables the sharing of resource between the institutions for the minimization of expense and also encourages learners by enhancing engineering education.